Systemic aspects of R&D policy: Subsidies for R&D collaborations and their effects on private R&D - Dirk Engel; Michael Rothgang; Verena Eckl (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2015)
The paper analyses how context and time dependent factors determine the impulse of R&D subsidies on firm behavior with respect to private R&D expenditures. Based on data from the German R&D survey, we combine propensity-score matching with a difference-in-difference-estimator in order to measure the causal influence of public direct R&D project funding on firm behavior. Our results indicate that (i) repeated participation in R&D projects on average leads to a higher increase in R&D expenditures than one-time funding; (ii) the aggregate effect of R&D funding on R&D expenditures of business firms is somewhat higher for business and business collaboration projects than for science and business collaboration projects; (iii) R&D expenditures of business firms that cooperate with science show a higher share of external R&D spending. Results of one particular cluster programme indicate that at least the short-term development of R&D does not so much depend on which programme direct R&D project funding is applied to.
Keywords: C14; C25; H50; O38; 330; R&D; public subsidies; collaboration; policy evaluation